ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL MATERI STATISTIKA PADA SISWA SMP KELAS VIII - Dinar Mediyani; Zanjabila Ar-rahiiqil Mahtuum (IKIP Siliwangi, 2020)
The focus in this study is to analyze and describe the difficulties experienced by students of class VIII in solving questions about statistical material. This research uses a qualitative approach with descriptive methods. Analysis of the results of student answers used according to three categories of learning difficulties according to Wood (2012). The data used in this study were the results of tests in the form of problem statements consisting of 5 items and were given to the subjects of this study as many as 5 students. The data obtained were then analyzed starting from data reduction, data exposure and conclusion drawing. The results of this study indicate that from the subject of 5 students only 69% of the questions were able to be solved and none of the students were able to solve the problem completely. This happens because the average student has difficulty understanding the purpose of the problem and it is difficult to determine how to solve it.